Influence of irrigation and row spacing on the growth, seed yield and active substance of milk thistle (Silybum marianum) - Karimzedah, G.; Omidbaigi, R.; D., Bakhshai (International Journal of Horticultural Science, 2001)
Milk thistle (Silybum marianum (L.) Gaertn) has been used in medicine since ancient times, but it has been cultivated as a medicinal plant only in recent decades. The ripe fruit of milk thistle contains flavonoids, which are used to prepare anti-hepatotoxic drugs. The main purpose of this study was to substantiate the effects of irrigation and row spacing on growth, seed yield and the content of active substances (silybin and silymarin) in milk thistle. The results showed that the suitable amount of irrigation was 20 mm and the appropriate row spacing was 25 cm.